Studies on the formulation and utilization of cassava flour - Pawar, Genevieve Dahlia (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirement for the award of the Degree of Master of Science in Food Science and Technology.